1983
DOI: 10.1111/j.1399-6576.1983.tb01958.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective PEEP in Acute Bilateral Lung Disease. Effect on Patients in the Lateral Posture

Abstract: Seven patients with acute respiratory failure due to diffuse and fairly uniform lung disease were studied during mechanical ventilation in the lateral decubital position with: (a) zero end-expiratory pressure (ZEEP) through a double-lumen oro-bronchial tube to permit a recording of the ventilation to each lung; (b) bilateral positive end-expiratory pressure (PEEP) of 1.2 kPa, with maintenance of ventilation distribution between lungs as observed during ZEEP; (c) selective PEEP of 1.2 kPa, applied to the depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The effects of selective PEEP in the lateral position may be assumed to reduce shunt and ventilation/perfusion mismatch. Although the detailed effects of differential ventilation with selective PEEP on ventilation/ perfusion matching remain hypothetical at present, the net effect in terms of reduced venous admixture and improved arterial oxygenation has in fact been demonstrated in patients with acute respiratory failure (8) and in clinically lung healthy patients during anaesthesia (9). The findings in the present study point to morphological changes underlying such improvements.…”
Section: Differential Ventilation With Selective Peep In the Lateral supporting
confidence: 47%
See 3 more Smart Citations
“…The effects of selective PEEP in the lateral position may be assumed to reduce shunt and ventilation/perfusion mismatch. Although the detailed effects of differential ventilation with selective PEEP on ventilation/ perfusion matching remain hypothetical at present, the net effect in terms of reduced venous admixture and improved arterial oxygenation has in fact been demonstrated in patients with acute respiratory failure (8) and in clinically lung healthy patients during anaesthesia (9). The findings in the present study point to morphological changes underlying such improvements.…”
Section: Differential Ventilation With Selective Peep In the Lateral supporting
confidence: 47%
“…8,9). During differential ventilation, the ventilators were electronically synchronized, thereby keeping the respiratory frequency equal and the start of inspiration simultaneous for both lungs.…”
Section: Anaesthesia and Ventilationmentioning
confidence: 99%
See 2 more Smart Citations
“…tion in cardiac output[99,100]. Opinions vary, however, as to the appropriate way to monitor improvement with PEEP therapy[101][102][103][104][105].Murray and colleagues[106] suggested that the PEEP level that results in the lowest PaF-1-co-) gradient is associated with the minimum intrapulmonary shunt value, without increasing dead space in a canine model of ARDS. Opinions vary, however, as to the appropriate way to monitor improvement with PEEP therapy[101][102][103][104][105].Murray and colleagues[106] suggested that the PEEP level that results in the lowest PaF-1-co-) gradient is associated with the minimum intrapulmonary shunt value, without increasing dead space in a canine model of ARDS.…”
mentioning
confidence: 99%